High-Performance Extrinsic Fabry-Perot Fiber Optic Acoustic Sensor Based on Au/PI Composite Film - Zekun Zhu; Hanyu Shuai; Kun Jia; Yuanyuan Sun; Bo Jia; Pengwei Zhou (IEEE Access, 2024)
This paper reports a novel Fabry-Perot fiber optic microphone based on Au/PI composite film, with an optimal F-P cavity length of $500 \, μ \text{m}$ , and the maximum extinction ratio (ER) obtained is about 12 dB. Besides, the sensor has flat response performance in the audio frequency range of 200–10 kHz, with a maximum signal-to-noise ratio (SNR) of 76 dB and a sensitivity of approximately 170 mV/Pa at the sound pressure level of 1000 Hz/94 dB, which is much higher than Brüel & Kjær’s electric microphone 4939. Within a certain range of sound pressure, there is a fine linear relationship between the output response of the sensor and the input sound pressure, with a fitting coefficient of 0.9987. The new diaphragm-type fiber optic microphone proposed in our work has superb economy, sensitivity, frequency response and linearity within the audible sound range, which is expected to achieve large-scale, low-cost fabrication and long-term stable application in audio detection and other fields.